Provision of central services in rural areas - Komar, Korana (Revija za geografijo, 2025)
This study explores demographic decline and the contraction of central services in the Zabok area of Hrvatsko Zagorje, Croatia. Using settlement-level analysis, a survey of residents aged 65+, and informal conversations, the relationship between long-term depopulation, ageing, and the spatial distribution of central services is examined. The results reveal spatial variation in the decline of education and retail, as well as differences in respondents’ ability to meet their daily needs, by settlement type. Findings highlight uneven development trajectories and the growing vulnerability of elderly populations.
Keywords: ageing; central services; centralne dejavnosti; depopulation; elderly; Mala mesta; Prebivalstvo; staranje; starejši